Healthcare Team Education Management for Improving Antihypertensive Medication Adherence Among Older Adults in Manado City, Indonesia - Rumampuk, Jimmy F.; Wullur, Mozes M.; Palilingan, Rolles N.; Rotty, Viktory N. J. (International Journal of Information Technology and Education, 2026)
This article analyzes the implementation of stunting management policies in Minahasa Regency. The study uses a descriptive qualitative approach to examine the policy process, the delivery of health services, community empowerment, health-supporting infrastructure, and determinant factors influencing policy performance. Data were obtained through observation, in-depth interviews, and documentation involving local government actors, district and village officials, health workers, community cadres, and community representatives. The analysis follows an interactive qualitative model consisting of data condensation, data display, and conclusion drawing. The findings show that stunting management has been implemented through structured planning, primary-health-service mechanisms based on puskesmas and posyandu, food supplementation, maternal and child health monitoring, community education, and village-level support. However, the implementation has not yet achieved full effectiveness because cross-sector integration remains weak, community participation is uneven, infrastructure and data quality are still limited, and program execution often depends on the capacity and commitment of local implementers. Determinant factors include policy communication, human and financial resources, bureaucratic coordination, implementer disposition, and socio-economic conditions. The article argues that stunting policy implementation requires stronger convergence governance, integrated local data, continuous cadre capacity building, culturally grounded health communication, and a family-centered service model that links specific nutrition interventions with sensitive interventions in sanitation, poverty reduction, education, and local economic empowerment.